Development of double burner smart electric stove powered by solar photovoltaic energy - Siddiqua, Sarah; Firuz, S.; Nur, B. M.; Shaon, R. J.; Chowdhury, Sheri Jahan; Azad, Akm M.M.Abdul Malek (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Global Humanitarian Technology Conference, GHTC 2016; Seattle; United States; 13 October 2016 through 16 October 2016 [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/GHTC.2016.7857319 The Journal's website is at: https://ieeexplore.ieee.org/document/7857319/